Methylation, crystallization and SAD phasing of the Csu pilus CsuC–CsuE chaperone–adhesin subunit pre‐assembly complex from Acinetobacter baumannii. Issue 8 (1st August 2017) - Pakharukova, Natalia; Tuittila, Minna; Paavilainen, Sari; Zavialov, Anton
Abstract : Archaic Csu pili mediate the formation of A. baumannii biofilms on abiotic surfaces. To determine the structural basis for biofilm formation, native and selenomethionine‐substituted pilus tip adhesin subunit CsuE complexed with the chaperone CsuC was produced in E. coli, purified and crystallized. Methylation of lysine residues was essential for crystallization of the complex. Initial phases were derived from selenomethionine‐based single‐wavelength anomalous dispersion. Abstract : Acinetobacter baumannii is one of the most difficult Gram‐negative bacteria to control and treat. This pathogen forms biofilms on hospital surfaces and medical devices using Csu pili assembled via the archaic chaperone–usher pathway. To uncover the mechanism of bacterial attachment to abiotic surfaces, it was aimed to determine the crystal structure of the pilus tip adhesin CsuE. The CsuC–CsuE chaperone–subunit pre‐assembly complex was purified from the periplasm of Escherichia coli overexpressing CsuC and CsuE. Despite the high purity of the complex, no crystals could be obtained. This challenge was solved by the methylation of lysine residues. The complex was crystallized in 0.1  M bis‐tris pH 5.5, 17% PEG 3350 using the hanging‐drop vapour‐diffusion method. The crystals diffracted to a resolution of 2.31 Å and belonged to the triclinic space group P 1, with unit‐cell parameters a = 53.84, b = 63.85, c = 89.25 Å, α = 74.65, β = 79.65, γ = 69.07°. Initial phases were derived from a single anomalous diffraction experiment using a selenomethionine derivative.